The Decriminalization of The Offense of Cultivating Type I Narcotics in Law Number 1 Of 2023 on The Indonesian Criminal Code - Nababan, Anisa Magdalena; Aprilianda, Nurini; Afandi, Fachrizal (IJBLE Scientific Publications Community Inc., 2025)
This thesis addresses the decriminalization of the cultivation of Group I narcotics following the revocation of Article 111 of the Narcotics Law by Article 622 paragraph (1) letter w of the National Criminal Code (KUHP Nasional) 2023. This situation, effective in 2026, creates a legal vacuum. This normative juridical research, employing statutory, historical, and conceptual approaches, aims to identify the ratio legis of previous regulations and propose an appropriate formulation. The findings show the ratio legis for regulating narcotic cultivation in the previous Narcotics Law was to break illicit supply chains and deter offenders, in line with international conventions. To fill the vacuum, the thesis recommends explicitly re-regulating the cultivation of Group I narcotics in Article 609 paragraphs (1)a and (2)a of the KUHP Nasional, with severe penalties, to criminalize and combat narcotics trafficking from its source.